KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR: KEWAJIBAN MORAL DAN SANKSI PERPAJAKAN - Kurniawati, Stephanie; Susanto, Yulius Kurnia (Fakultas Ekonomi, Program Studi Akuntansi, 2021)
The objective of the research is to get empirically evidence of the influence of the awareness, moral obligations, service quality, sanctions, knowledge, and drive thru samsat sytems on taxpayer compliance. Population used in this research is vehicle’s taxpayer in Special Capital Region of Jakarta. Data collecting using questionnaires distributed through google forms to the respondents. The number of the sample consists of 119 respondents. Sampling method used in this research is convenience sampling and the data analysis method used is multiple linear regression. The result showed that moral obligations and sanctions have influenced on taxpayer compliance. While awareness, service quality, knowledge, and drive thru samsat sytems have not influenced on taxpayer compliance in Special Capital Region of Jakarta. The higher of moral obligations and sanctions, the higher of taxpayer compliance in Special Capital Region of Jakarta in paying motor vehicle taxes.